2016
DOI: 10.14581/jer.16011
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsive Effects of Licofelone on Status Epilepticus Induced by Lithium-pilocarpine in Wistar Rats: a Role for Inducible Nitric Oxide Synthase

Abstract: Background and PurposeStatus epilepticus (SE) is a neurological disorder with high prevalence and mortality rates, requiring immediate intervention. Licofelone is a cyclooxygenase (COX) and 5-lipoxygenase (5-LOX) inhibitor, which its effectiveness to treat osteoarthritis has been approved. Increasing evidence suggests an involvement of COX and LOX enzymes in epileptic disorders. Thus, in the present study we investigate possible effects of licofelone on prevention and termination of SE. We also evaluated wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 56 publications
(54 reference statements)
2
13
0
Order By: Relevance
“…Pre-treatment with 7-NI did not change seizure susceptibility significantly, but coadministration of AG and licofelone exerted anticonvulsive effects. These data suggested that the NO pathway especially iNOS contributes to the anticonvulsive effects of licofelone (52). (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Pre-treatment with 7-NI did not change seizure susceptibility significantly, but coadministration of AG and licofelone exerted anticonvulsive effects. These data suggested that the NO pathway especially iNOS contributes to the anticonvulsive effects of licofelone (52). (Fig.…”
Section: Discussionmentioning
confidence: 77%
“…The inflammatory response following status epilepticus causes activation of inducible nitric oxide synthase (iNOS) and iNOS-derived nitric oxide (NO) reacts with O 2 - to form the peroxynitrite and contributes the severity of oxidative stress in kainic-acid induced experimental status epilepticus in our previous studies [ 25 , 26 , 27 , 28 ]. Several studies with a various animal model of status epilepticus such as pilocarpine-induced, pentylenetetrazole-induced, diisopropylfluorophosphate, lithium-pilocarpine model, also demonstrated the critical role of NO-related pathway and neuro-inflammation contributing to neuronal damage [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pilocarpine, lithium chloride, sumatriptan, GR‐127935, scopolamine methyl bromide, L‐NAME, 7‐nitroindazole, aminoguanidine, ketamine, and xylazine were injected intraperitoneally (i.p.). The doses of drugs, route of administration, and the time of injection were selected based on previous experiments, our pilot studies, and pharmacokinetic consideration [20,23,27,31].…”
Section: Methodsmentioning
confidence: 99%
“…Nitric oxide (NO) is produced from the amino acid L‐arginine through activity of different isoforms of NO synthase (NOS) enzymes including endothelial NO (eNOS), inducible (iNOS), and neuronal (nNOS). There is ample evidence that NO plays a role in different types of seizure such as SE [26,27]. At the early stages of SE, nNOS is responsible for NO overproduction; and iNOS intervenes in continuous excess NO generation for a long time, resulting in neuronal cell death in rodents [28].…”
Section: Introductionmentioning
confidence: 99%